An Exploratory Comparative Study on Eco-Impact of Paper and Plastic Bags (Journal of Fiber Bioengineering and Informatics, 2018)
Today there are varieties of comments prevailing among people who use Plastic and Paperbags for their shopping needs. A few people support Plastic bags with their own justifications andothers support Paper bags. This is a hot topic of today and arguments are going up and down to deducewhich one is better in terms of environmental impact, but some people abstain from this issue bychoosing the other option of going with reusable bags. This exploratory study is attempted to inferthe environmental concerns made by these bags. The two common grocery bags of today - Paper &Plastic bags are compared in this study. Two imperative measures - total amount of energy used by abag to get it manufactured and the amount of pollutants emitted during the manufacturing phase of abag - are chosen as data for Life Cycle Inventory (LCI). To arrive at a clear state of conclusion withrespect to environmental impact made by these two bags, life cycle impact assessment (LCIA) studywas accomplished. Evolvement of Life Cycle Assessment (LCA) study from the data available on thiscontext is the crux of this study. The Eco-indicator 99, damage oriented method for LCIA in SIMAPRO7.1 tool is used to assess the environmental impact made by these two grocery bags. The single scorevalues calculated by the Eco-indicator 99 is considered as a directive to compare the environmentalimpact made by these and a detailed explanation of results is also dealt with in this paper. As far as theLife cycle energy analysis and amount of pollutants produced from these two bags are concerned, aplastic bag simply scores out a paper bag. The impact assessment results are also in line to support theplastic bags over paper bags. However, this conclusion has been drawn on the basis of the secondarydata chosen for LCI and the results provided by the software which also has certain hypotheses andassumptions.